The utility of the heart rate - power output relationship to monitor short-term training adaptations in trained athletes - Black, M. J.; Norris, S. R. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The heart rate (HR) response to exercise has been used extensively to monitor training adaptations. In trained athletes, changes in HR at specific power outputs are often considered inversely proportional to changes in stroke volume (SV). However, little information exists regarding the implications of changes in the slope of the HR versus power output (HR-PO) relationship. One purpose of this study was to determine the source of rapid changes in the HR-PO relationship in trained endurance athletes. Methods Ten trained cyclists underwent 7 consecutive days of intense training consisting of an incremental exercise test (2 min·stage-1) to maximum power output (MPO), 3-min repetitions at 100, 95, 90, 85 and 80% MPO, 5 3-min repetitions at 150% MPO, and 20 min cycling at the first ventilatory threshold. During each incremental test, HR was recorded for the last 10 seconds of each workload, and the slope and intercept of the HR-PO relationship were determined. Three minutes after each incremental test, a blood lactate sample was procured. Resting plasma volume (PV), exercising cardiac output (Q) and VO2 from rest to MPO were determined the day before (PRE) and the day after (POST) the training cycle. Plasma volume was determined through intravenous injection of indocyanine green dye. Cardiac output was determined through an acetylene breathing technique. All exercise testing and training was performed on a mechanically-braked cycle ergometer. Results A significant increase in PV (6.9%) was found from PRE to POST training, while Q and VO2 were not different at any exercise intensity. Compared to PRE, POST Q was attained with a lower HR and higher SV. The increased reliance on SV to attain Q was intensity-dependent, with the greatest PRE-POST increase in SV (9.6%) occurring at a Q of approximately 24 L·min-1 (Fig. 1). There was a weak correlation between the increase in PV and the increase in maximum SV (r2 = 0.26; n = 9). The intercept of the HR-PO relationship was unchanged throughout training, while the slope of the relationship was significantly less by the third day of training. The decrease in the slope of the HR-PO relationship persisted until the end of the training cycle. A significant decrease in HR at MPO was also found by the third day of training. No significant change in MPO or peak lactate was found throughout the training cycle. Discussion/Conclusion The HR-PO relationship accurately predicted changes in SV following training. The decrease in the slope of the HRPO relationship suggests an improved ability to increase SV with increasing exercise intensities. The weak relationship between SV and PV suggests changes in contractility may play an important role in such adaptations. The increase in submaximal and maximal SV did not translate to an increase in MPO, presumably because of the decrease in the attainable maximum HR. The maintenance of peak blood lactate suggests muscle glycogen storage was not a factor for this limitation. Therefore, the utility of the HR-PO relationship to predict overall training adaptations requires the test be performed to maximum heart rate.